Deep Vein Thrombosis Associated with Protein C and Protein S Deficiency: An Unusual Cause of Acute Abdomen - Doganay, Selim; Sonmezgoz, Fitnet; Sen, Yasar; Kocakoc, Ercan (Wiley, 2011)
Deep venous thrombosis is an extremely rare cause of acute abdomen and is often difficult to diagnose. Protein C and protein S deficiencies are rare genetic abnormalities that predispose the patient to thrombophilia and lead to thrombosis. We report the case of a previously healthy 7-year-old boy with iliofemoral thrombosis due to protein C and protein S deficiencies mimicking acute abdomen. (C) 2010 Wiley Periodicals, Inc. J Clin Ultrasound 39:287-289, 2011; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI: 10.1002/jcu.20771
Keywords: acute abdomen; protein C deficiency; protein S deficiency; computed tomography; ultrasonography; deep vein thrombosis